Graphic organizers as a cognitive strategy to develop vocabulary amongst ninth-year b students at colegio de bachillerato 27 de Ferrero of the city of Loja during the 2016-2017 school year - Cueva Castillo, Andrea Isabel (2018)
The main purpose of the research was to develop vocabulary through graphic organizers as a cognitive strategy amongst ninth-year B students at Colegio de Bachillerato 27 de Febrero during the 2016-2017 school year. The essential methods used in the investigation were the following: scientific, statistic, descriptive and synthetic-analytical. They served to gather information, analyze and interpret the results of the research. The instruments used to collect the data were: tests, questionnaires and field notes given to twenty-six students. The results revealed a noticeable progress in vocabulary development in these five aspects: idioms, hyponyms, cognates, word meaning and collocations. In conclusion, the use of graphic organizers was effective and successful in developing students’ vocabulary due to the fact that they were capable of identifying and understanding the words without problems, demonstrating proficiency in their correct use. This strategy also gained learners’ interest and motivated them to learn vocabulary